The Employee Value Creation, Governance Structure and Financial Sustainability of Nigerian Listed Deposit Money Banks - Oladejo, Titilayo Moromoke (International Review of Management and Marketing, 2026)
This paper examined the impact of employee value creation on the financial stability and profitability of the listed deposit money banks in Nigeria moderated by governance structure. The study covers 12 banks out 14 banks whose complete data are between 2015 and 2024. It uses ex-post facto research design, panel data regression and Panel Corrected Standard Errors (PCSE) to control for auto serial correlation. The value of employees is measured in employee value added share (EVA), revenue per employee (RPE), and the human capital efficiency (HCE). Governance proxies are Board size (BS) and independence of remuneration committee (RCI). The Altman Z -score and the return on sales (ROS) are used to evaluate firm performance. The findings indicate that HCE positively and significantly impacts the measure of Z -score. Both HCE and RPE increase profitability in a positive and significant way. The interaction of BS and HCE as moderating effect diminishes stability and profitability, this suggest that excessive boards size constrain the benefit of employee efficiency. The research paper points to the necessity to enhance the productivity of human capital, streamline the board structures, increase the efficiency of employee value creation through good governance to retain long-term financial stability